Exchange Rate Overvaluation and Trade Protection : Lessons from Experience - Shatz, Howard J.; Tarr, David G. (World Bank, Washington, DC, 2015)
Despite a trend toward more flexible rates, more than half the world's countries maintain fixed or managed exchange rates. In the 1980s and 1990s, developing countries as a group progressively liberalized their trade regimes, but some governments defend their exchange rate in actions that run counter to long-run plans for liberalization. Without discussing the relative merits of fixed and flexible exchange rate systems, the authors note that exchange rate management in many countries has resulted in overvaluation of the real exchange rate. Roughly twenty five percent of the countries for which data are available have overvalued exchange rates, with black market premiums from 10 percent to more than 100 percent. After surveying the literature, the authors present lessons from experience about what has worked (or not) in response to crises involving external shocks and external trade deficits - and why. Trying to defend an overvalued exchange rate with protectionist trade policies is a classic pattern, but experience shows such protection does significantly retard the country's growth, and delay its integration into the world trading community. In fact, and overvalued exchange rate is often the root cause of protection, preventing the country from returning to more liberal trade policies that allow growth and integration into the world community without exchange rate adjustment. Most developing countries have downward price and wage rigidities and, with an external trade deficit, require some form of nominal exchange rate adjustment to restore external equilibrium. The authors present cross-country econometric and case study evidence - citing examples from Argentina, Chile, Ghana, the Republic of Korea, Malaysia, Turkey, Uruguay, and Sub-Saharan Africa (including the CFA zone) - that overvalued exchange rates reduce economic growth. Defending the exchange rate, they show, has nor no medium-term benefits, since falling reserves will eventually force devaluation. Better to have devaluation occur without further debilitating losses in reserves and lost productivity because of import controls. After devaluation the exchange rate will reach a new equilibrium, strongly influenced by government and central bank policies.